Consumer and Wholesale Prices in a Model of Price Behavior by Stage of Processing - Popkin, Joel (The Review of Economics and Statistics, 1974)
THIS paper was undertaken for two purposes: (1) to uncover additional quantitative information about the structure of price behavior and (2) to see the extent to which such information could be enlarged as a result of studying price data arrayed by stage-ofprocess. Wholesale price indexes of the Bureau of Labor Statistics (BLS) have long been arranged this way, among others, and components of the Consumer Price Index can be developed that relate to these wholesale indexes. The study of price indexes by stage-of-process can be viewed as an approximation to the type of study that could be conducted in an inputoutput framework, if time-series data were available for I-0 industries. The research consisted of testing theories of price behavior whose determinants could be measured for sectors relevant to the explanation of price behavior by stage-of-process (these are shown in figure 1). This led to the selection of a set of price equations for consumer and producers' goods and their intermediate inputs. Additional equations were estimated for service prices and wages so that a nearly complete price sub-model could be developed. This model was then used to explore the structure of price determination. The stage-of-process approach differs from other studies of price behavior, most of which have sought to explain the deflator for private GNP and its components or the wholesale price index (WPI) for the manufacturing sector and its major subdivisions durable and nondurable goods. Such studies have not used the most relevant price series. The series that should be used are those reflecting the prices at which firms in a sector sell their output to customers outside of the sector. These prices are reflected more closely at high levels of aggregation by using stage-of-processing indexes rather than any other components of the WPI. In a recent review of empirical research on price behavior, Nordhaus (1972) concludes that most specifications and interpretations of price models have proceeded without the benefit of formal theory. While the testing of hypotheses is the focus of the present research, the effort encounters the common difficulties in so doing the lack of precise specification of any but the most simplistic models, poor or missing data, and estimation problems. To preview a conclusion, price behavior is difficult to explain and no one theory can be shown to be superior to all others. At least for the present, it appears that forecasting and policy formulation based on the structure of price determination must combine theory with professional judgments about which reasonable persons may disagree. Given these circumstances, the results of exploring price data by stage-of-process yields some interesting and potentially useful results.